Demonstration of simultaneous quantum steering by multiple observers via sequential weak measurements - Choi, Yeon-ho; Hong, Seongjin; Pramanik, Tanumoy; Lim, Hyang-tag; Kim, Yong-su; Jung, Hojoong; Han, Sang-wook; Moon, Sung; Cho, Young-wook (OPTICAL SOC AMER, 2020)
Quantum correlation is a fundamental resource for various quantum information tasks. It is thus of importance to share the correlation to utilize it for many parties, but sharing quantum correlation among multiple parties is strictly restricted by the well-known monogamy relations. Nonetheless, this restriction can be relaxed when weak measurements are employed. Here, we experimentally demonstrate multiple-observer quantum steering by exploiting sequential weak measurements. Specifically, we observe simultaneous triple violations of the quantum steering inequality among four observers for a bipartite entangled system. Our results not only provide fundamental insights into the relation between quantum steering and measurement disturbance, but also suggest that quantum steering might be repeatably exploited to find applications to, for example, unbounded randomness certification and sharing secret keys among multiple parties simultaneously. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement